2019
DOI: 10.1063/1.5093158
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution for the flow of second grade fluid over a stretching sheet

Abstract: This article addresses the phenomenon of boundary layer flow and heat transfer in respect of the motion of second grade viscous fluid over an unsteady stretchable surface. Optimal variational iteration method (OVIM) is employed to solve the governing differential equation. OVIM is the modified version of variational iteration method (VIM). The convergence of the obtained solution as well as the effect of pertinent parameters on the velocity components are discussed, tabulated, and graphed. Behaviour of coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…It is observed that greater values of and leads to higher estimates of skin friction . The comparison between the current findings of the second-grade fluid parameter influence on skin friction and Rafiq et al 54 is shown in Table 2 . The results of the present study shows great harmony with previous data.…”
Section: Numerical Resultsmentioning
confidence: 74%
“…It is observed that greater values of and leads to higher estimates of skin friction . The comparison between the current findings of the second-grade fluid parameter influence on skin friction and Rafiq et al 54 is shown in Table 2 . The results of the present study shows great harmony with previous data.…”
Section: Numerical Resultsmentioning
confidence: 74%
“…The accuracy and consistency of the current numerical solution are gauged by means of a quantitative comparison with a prior study conducted by Rafiq et al 47 This comparison serves to authenticate the precision of the present numerical data. The results are quantitatively assessed by comparing them against the data from the aforementioned study, as demonstrated in Table 1.…”
Section: Verification Of the Numerical Codementioning
confidence: 69%
“…Figures 2-8 examine the performance of parameters across subjective fields. The current results are compared with Rafiq et al [31] and Jamshed et al [32] as described in Table 3. Table 1 contains Figure 2 analyzes the effect of suction parameters via the velocity of fluid.…”
Section: Resultsmentioning
confidence: 95%